Reviving the Classical Paradigm: Exploring the Timeless Principles of Classical Education in the Modern World - Nananukul, Naramethi; Nafi Annury, Muhammad; Minh Hoangh, Trinh; Soontarin, Nupap (Global Synthesis in Education Journal, 2024)
This mixed-methods study examines the relationship between Project-Based Learning (PBL) and critical thinking development in undergraduate education. A total of 168 students from three universities participated in the research, which employed a mixed-methods design involving pre-post assessments, project artifact analysis, interviews, and focus group discussions across STEM, social sciences, and humanities disciplines. The results indicate statistically significant improvements in critical thinking scores, with mean scores increasing from 68.4 to 74.9 (t(167) = 8.42, p < .001, Cohen's d = 0.54). Notably, humanities students demonstrated the most substantial gains (M = 8.2 points), while analysis and evaluation subscales showed the most significant enhancements. The findings provide compelling evidence that PBL represents a sophisticated pedagogical approach for developing critical thinking skills, facilitating a dynamic, contextual process of cognitive expansion that transcends traditional disciplinary boundaries